2021
DOI: 10.3390/vaccines9121439
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Development of SARS-Coronavirus-2-Specific Cellular Immunity, and Central Memory CD4+ T-Cell Responses Following Infection versus Vaccination

Abstract: Memory T-cell responses following infection with coronaviruses are reportedly long-lived and provide long-term protection against severe disease. Whether vaccination induces similar long-lived responses is not yet clear since, to date, there are limited data comparing memory CD4+ T-cell responses induced after SARS-CoV-2 infection versus following vaccination with BioNTech/Pfizer BNT162b2. We compared T-cell immune responses over time after infection or vaccination using ELISpot, and memory CD4+ T-cell respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Positive responses were defined by stimulation index (stimulated spot-forming units/2 × 105 cells divided by unstimulated spot-forming units/2 × 105 cells) as clearly positive with a stimulation index of ≥7 and clearly negative with a stimulation index of ≤3. Samples with values that fell in between were defined as negative unless the unstimulated control value was >2 staining units/2 × 105 cells and the stimulation index was >3, as described by the manufacturer ( 12 ). In the present manuscript, measurements are shown as stimulation index (SI) values and not as spot-forming units due to the different background levels in the IFN-γ and IL-2 assays.…”
Section: Methodsmentioning
confidence: 99%
“…Positive responses were defined by stimulation index (stimulated spot-forming units/2 × 105 cells divided by unstimulated spot-forming units/2 × 105 cells) as clearly positive with a stimulation index of ≥7 and clearly negative with a stimulation index of ≤3. Samples with values that fell in between were defined as negative unless the unstimulated control value was >2 staining units/2 × 105 cells and the stimulation index was >3, as described by the manufacturer ( 12 ). In the present manuscript, measurements are shown as stimulation index (SI) values and not as spot-forming units due to the different background levels in the IFN-γ and IL-2 assays.…”
Section: Methodsmentioning
confidence: 99%
“…showed that vaccination and infection induced comparable levels of specific SARS-CoV-2 CD4+ T cells after three months in addition to comparable proportions of specific central CD4+ memory T cells. In contrast, the proportion of specific effector CD4+ memory T cells was significantly lower and specific effector CD4+ memory T cells were higher after infection than after vaccination [106].…”
Section: Vaccine-induced Immunity To Sars-cov-2mentioning
confidence: 72%
“…The assessment criteria for the ELISpots were a minimum of 50 SFU in the positive control and a maximum of 10 SFU in the negative control according to the manufacturer’s definitions (19, 20). When those criteria were fulfilled, the stimulation index (SI) was calculated by dividing the mean SFU numbers in the antigen-specific wells with the mean SFU numbers of the negative control.…”
Section: Methodsmentioning
confidence: 99%